Social behaviour of the Freckled Duck Stictonetta naevosa with particular reference to the axle-grind - Fullagar, P J; Davey, C C; Rushton, D K (Wildfowl, 1990)
We describe a display posture and call, the axle-grind, of the Freckled Duck. We observed it only in males and it was usually, but not always, directed towards females. The display was first observed in young males reared in captivity when they were five months old. The development of the call was studied and our findings are illustrated by sonagrams. We confirm that a typical duck-like pre-flight signal occurs in the Freckled Duck and discuss other social signals and interactions seen in this aberrant duck.